2022
DOI: 10.3389/fcimb.2022.893294
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Random Forest Algorithm in Predicting Severe Acute Pancreatitis

Abstract: Background and AimsThis study aimed to develop an interpretable random forest model for predicting severe acute pancreatitis (SAP).MethodsClinical and laboratory data of 648 patients with acute pancreatitis were retrospectively reviewed and randomly assigned to the training set and test set in a 3:1 ratio. Univariate analysis was used to select candidate predictors for the SAP. Random forest (RF) and logistic regression (LR) models were developed on the training sample. The prediction models were then applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 98 publications
(124 reference statements)
0
15
0
Order By: Relevance
“…In recent years, a number of diagnostic and prognostic markers, both alone and in combination, have been tested on individuals diagnosed with AP [16][17][18]. After elevated RDW was established as a predictor of poor outcomes in chronic heart failure in 2007, multiple studies have shown that it is signifcantly related to short-term mortality outcomes in a range of infammatory disorders [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of diagnostic and prognostic markers, both alone and in combination, have been tested on individuals diagnosed with AP [16][17][18]. After elevated RDW was established as a predictor of poor outcomes in chronic heart failure in 2007, multiple studies have shown that it is signifcantly related to short-term mortality outcomes in a range of infammatory disorders [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…These newly identified studies were screened based on the inclusion and exclusion criteria. Finally, a total of 33 original studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were included. The literature screening process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten [ 23 , 24 , 26 , 27 , 30 , 31 , 34 , 35 , 40 , 41 ] studies were multicenter studies, while two studies [ 18 , 20 ] collected subjects from databases. Eleven studies [ [14] , [15] , [16] , 18 , [20] , [21] , [22] , 25 , 26 , 31 , 35 ] considered overfitting, and k-fold cross-validation was primarily used. The original studies collectively constructed 55 new machine-learning models and evaluated three primary clinical scales: APACHE II, BISAP, and Ranson.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between model errors and fitted variables is depicted by cross-validation curves. Multiple groups of different training and verification are performed on the model in this study by using different training sets and verification set division through the implementation of ten-fold cross-validation, to deal with the problems of one-sided test results and insufficient data [20].…”
Section: Random Forestmentioning
confidence: 99%